2021
DOI: 10.1080/14786419.2021.1897589
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antifungal activity of Zanthoxylum riedelianum stem bark essential oil

Abstract: The phytopathogenic fungi Sclerotinia sclerotiorum and Rhizopus stolonifer infect different crop plants. Essential oils have been used as an alternative to chemical control methods.Therefore, the objective of this study was to analyze the essential oil chemical composition of the stem bark of Zanthoxylum riedelianum (ZREO) and evaluate its antifungal potential. The ZREO obtained by hydrodistillation was analyzed using gas chromatography coupled to mass spectrometry and evaluated for in vitro antifungal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Most of the Zanthoxylum seasoning oil sold in the market today was made by directly soaking peppers in vegetable oil. However, in the previous research on the processing of Zanthoxylum seasoning oil, it was found that the numb taste and aroma components would be partially lost during its processing and storage [8], both of which were important indicators for the quality evaluation of Zanthoxylum seasoning oil. Therefore, how to increase the aroma of Zanthoxylum seasoning oil and its persistence of numb taste was particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the Zanthoxylum seasoning oil sold in the market today was made by directly soaking peppers in vegetable oil. However, in the previous research on the processing of Zanthoxylum seasoning oil, it was found that the numb taste and aroma components would be partially lost during its processing and storage [8], both of which were important indicators for the quality evaluation of Zanthoxylum seasoning oil. Therefore, how to increase the aroma of Zanthoxylum seasoning oil and its persistence of numb taste was particularly important.…”
Section: Introductionmentioning
confidence: 99%